Asuhan Keperawatan Pada Ny.M dengan Ulkus Diabetikum Di Rumah Sakit Reksodiwiryo Padang - ade rahman (Jurnal Ilmiah Cerebral Medika, 2019)
Diabetes Mellitus (DM) is a disease characterized by an increase in chronic blood glucose levels. Diabetic ulcers are a complication of diabetes mellitus. The purpose of this study was to determine how the implementation of nursing care in diabetic ulcer patients. The research design used is a case study with a qualitative research type, conducted in the walnut room with an implementation time of 30 May – 1 June 2019. The data collection instruments used were medical-surgical assessment formats, and physical examination tools. The analysis used is to analyze all the findings at the stages of the nursing process by using nursing concepts and theories in Diabetic Ulcer patients. The results of the study found that Mrs. M complained of pain in the wound, a blackish red wound appeared on the right big toe, the patient seemed to be assisted with activities because of pain in the wound area. According to the theory of nursing diagnoses that may appear as many as five diagnoses, in this case 3 diagnoses were found, namely pain, damage to skin integrity and activity intolerance. The nursing plan is in accordance with the NIC, while the nursing evaluation is in accordance with the NOC where 1 diagnosis is resolved and 2 diagnoses are partially resolved. Future hopes for nurses to be able to maintain and maximize minimal nursing actions and also maintain good communication so that they can provide optimal nursing care for patients with diabetic ulcers.